A proteção do consumidor turista no âmbito do mercosul - Reul, Rodrigo Araújo (2018)
The purpose of this dissertation is to present the need for studies related to the protection of the tourist consumer, paying particular attention to the reality of the consumer market within the MERCOSUR Common Market, demonstrating, through analysis of the country ' Of the market and precedents of jurisprudence, the need of better adaptation of the consumerist standards for the protection of the tourist consumer. Thus, it is approached, initially, the foundation about concepts inherent to the relation of consumption, starting from a historical analysis. Subsequently, tourism, its regionalization, development and the National Chamber of Consumer Relations in this field are studied. It also analyzes the existing regulations for the creation and operation of MERCOSUR, aiming to highlight precepts related to the right to development related to the regional integration of markets. Finally, we present proposals for the implementation of normative adjustments and the creation of effective and sustainable public policies for the promotion of the protection of the interests of the tourist consumer in a national plan and in the unified market that Brazil integrates.